2015
DOI: 10.5194/acp-15-10071-2015
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence vertical structure of the boundary layer during the afternoon transition

Abstract: Abstract.We investigate the decay of planetary boundary layer (PBL) turbulence in the afternoon, from the time the surface buoyancy flux starts to decrease until sunset. Dense observations of mean and turbulent parameters were acquired during the Boundary Layer Late Afternoon and Sunset Turbulence (BLLAST) field experiment by several meteorological surface stations, sounding balloons, radars, lidars and two aircraft during the afternoon transition. We analysed a case study based on some of these observations a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 49 publications
9
44
0
Order By: Relevance
“…Moreover, Darbieu et al (2015) also found steeper slopes in spectra derived from aircraft measurements. Lothon et al (2009) and Darbieu et al (2015) assume that a steeper slope could also be caused by asymmetric convective structures, i.e., by anisotropy of the w field.…”
Section: Characteristics Of Vertical Velocity Datamentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, Darbieu et al (2015) also found steeper slopes in spectra derived from aircraft measurements. Lothon et al (2009) and Darbieu et al (2015) assume that a steeper slope could also be caused by asymmetric convective structures, i.e., by anisotropy of the w field.…”
Section: Characteristics Of Vertical Velocity Datamentioning
confidence: 95%
“…Lothon et al (2009) and Darbieu et al (2015) assume that a steeper slope could also be caused by asymmetric convective structures, i.e., by anisotropy of the w field.…”
Section: Characteristics Of Vertical Velocity Datamentioning
confidence: 99%
“…This could be related to the quasi-stationary behaviour discussed in Darbieu et al (2015) and Nilsson et al (2015a), where no changes in turbulence structure or characteristics are evident after normalization by the decreasing surface sensible heat fluxes. The difficulties increase in the very late afternoon.…”
Section: Afternoon Transitionmentioning
confidence: 99%
“…The layer between the pink and the red symbols was named the pre-residual layer by Nilsson et al (2015b). It is characterized by very low turbulence and results from the adjustment of turbulence to the decreasing surface fluxes (Darbieu et al, 2015). Figure 11 presents the variations of the time when the virtual temperature flux (which is a combination of the surface sensible heat flux and the latent heat flux) becomes negative, t_Hv0, through the IOPs and the various points.…”
Section: Afternoon Transitionmentioning
confidence: 99%
“…Recent simulations (Darbieu et al, 2015) have also been used to study TKE and other turbulence characteristics such as anisotropy, evolution of spectra and integral length scales during the afternoon transition. This was also studied by Pino et al (2006) using LES by prescribing an instantaneous change to zero-buoyancy flux, similar to Nieuwstadt and Brost (1986) but with the additional effect of shear production.…”
mentioning
confidence: 99%